From informatics to quantum informatics - Gruska, Jozef (2006)
Quantum phenomena exhibit a variety of weird, counter intuitive, puzzling, mysterious and even entertaining effects. Quantum information processing tries to make an effective use of these phenomena to design new quantum information processing and communication technology and also to get a better understanding of quantum and information processing worlds. During the recent years, exploration of the quantum information processing and communication science and technology got a significant momentum, and it has turned out quite clearly that paradigms, concepts, models, tools, methods and outcomes of informatics play by that a very important role. They not only help to solve problems quantum information processing and communication encounter, but they bring into these investigations a new quality, and to such an extend, that one can now acknowledge an emergence of a quantum informatics as of an important new area of fundamental science with contributions not only to quantum physics, but also to (classical) informatics itself. The main goal of this paper is to demonstrate the emergence of quantum informatics, as of a very fundamental, deep and broad science, its outcomes and especially its main new fascinating challenges, from informatics and physics point of view. Especially challenges in the search for new primitives, computation modes, new quality concerning efficiency and feasibility of computation and communication, new quality concerning quantum cryptographic protocols in a broad sense, and also in a very new and promising area of quantum formal systems for programming, semantics, reasoning and verification. The paper is targeted towards informaticians that are pedestrians in the mysterious quantum world, but would like to see what are new driving forces in informatics, where they drive us, why and how. In the paper, oriented towards broad audience, main mysteries, puzzles and specific features of quantum world are dealt with as well as basic models, laws, limitations, results and the state-of-the-art of quantum information processing and communication.